Understanding Compulsive Buying Tendencies: The Roles of Attitude Towards Money - Susiloadi, Priyanto; Renanita, Theda (Indigenous, 2023)
Abstract. Compulsive behaviour is important to be scientifically understood since it is a form of behaviour that negatively impacts the consumer. A previous study showed that a compulsive person has low self-control, compulsive personality tendencies, and low self-esteem. This study tested the relationship between behaviour towards money and compulsive buying tendencies behaviour towards money from the power prestige dimension, retention time, distrust, and anxiety. The participants of this study are 275 people. The analysis is done by testing the structural model with a partial least square. The research result showed retention time (T-statistics= 2.330, p= .020, original sample = -.121) and anxiety (T-statistics= 3.374, p= .001, original sample = .258) have effects on compulsive buying tendencies. Meanwhile, the power prestige and distrust dimension do not affect buying tendencies. The results of this study have implications for the importance of developing interventions to prevent the adverse effects of compulsive buying through increased financial planning and decreased financial anxiety.Keywords: Attitude towards money; consumer; compulsive buying; path analysis.